Integrated EM4-based anaerobic and aerobic wastewater treatment for sustainable tofu industry effluent management - Marsyea, Rihlah Fahiranti; Oktiawan, Wiharyanto; Djaeni, Moh. (Waste Handling and Environmental Monitoring, 2025)
Background: The Tahu Sehat Sari industrial area in Cokro Village is one of the largest tofu manufacturers, processing 3 tons of soybeans daily with 88 employees. However, wastewater quality tests reveal that the effluent exceeds regulatory limits set by Central Java Regional Regulation No. 5 of 2012, with BOD at 422.5 mg/L, COD at 845 mg/L, and TSS at 1940 mg/L. Effective wastewater treatment is necessary to ensure compliance with environmental standards and minimize pollution. Methods: This study evaluates wastewater treatment alternatives, including Anaerobic Digester, Anaerobic Biofilter, and Aerobic Biofilter, with the addition of Effective Microorganisms 4 (EM4) to enhance organic waste degradation. Wastewater samples were tested for COD, BOD, and TSS levels before and after treatment to assess removal efficiency. Findings: The implementation of EM4 significantly improved wastewater quality, achieving an 86% reduction in COD with a 0.3% EM4 concentration in aerobic treatment. EM4’s fermentation bacteria effectively minimized organic contaminants. The selected treatment methods—Anaerobic Digester, Anaerobic Biofilter, and Aerobic Biofilter—proved suitable for treating tofu wastewater, with final effluent concentrations of COD at 2.4 mg/L, BOD at 0.3 mg/L, and TSS at 35 mg/L, meeting regulatory standards. The estimated cost for the construction of a Wastewater Treatment Plant (WWTP) is IDR 1,177,378,400, with monthly operation and maintenance expenses of IDR 6,110,297. Conclusion: The study confirms that an integrated wastewater treatment system using anaerobic and aerobic biofilters combined with EM4 is effective in reducing organic waste contamination in tofu industry effluent. Further assessment of land use and distribution systems is recommended to optimize wastewater management. Novelty/Originality of this article: This research contributes to sustainable wastewater treatment in tofu production by integrating EM4 technology with anaerobic and aerobic filtration, achieving high pollutant removal efficiency. The study also provides a financial analysis of WWTP implementation, highlighting its feasibility for similar small and medium enterprises.